Military Pedagogical Science: Problems And Solutions - Makhmudov Rozmet Muratovich; Xaydarov Ismail Ollokulovich; Abdulaziz Abdurakhmanovich Karaboev (Zien Journals, 2023)
The article discusses changes in military education and training, the place and role of military pedagogy in military professional activities, the attitude of officers to ethics and discipline, the necessary qualities in the management of military units, issues of pedagogical and psychological impact on military personnel.
Keywords: military pedagogy; pedagogical activity; military education and training; managerial behavior